A Comparative Analysis of the Original and Translated Lyrics of "What Else Can I Do?" From Disney’s Encanto 2021 - Shifa Achmadah Syauqi; Otong Setiawan Djuharie (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This research analyzes the translation strategies applied in the Indonesian version of the song "What Else Can I Do?" from Disney's animated film Encanto (2021). Using Peter Newmark’s translation theory, the study compares 26 selected lines from the original English lyrics with their Indonesian translations, focusing on four methods: literal, faithful, free, and communicative translation. The analysis, conducted through a qualitative descriptive approach, reveals that each method was strategically applied depending on the content and context of each line, aiming to maintain meaning, rhythm, and emotional impact. The results highlight the complexity of song translation, particularly the balance between linguistic accuracy and cultural adaptation in audiovisual media.